Diseño y construcción de un dispositivo de disipación de energía a la entrada del canal experimental de pendiente variable de la ECI (2013)
In hydraulics, different phenomena are presented, in which the hydraulic engineer must determine the causes that generate the problem and the most adequate alternatives to give an optimal solution or minimize the effects that they can cause to a given medium. It is important the theoretical and experimental study of the different hydraulic parameters to make the best decisions. Based on the above, the main purpose of this project is to analyze different alternatives to build a device, which allows to adequately dissipate the kinetic energy present in the feed pipe at the entrance of the experimental channel of the ECI. It should be taken into account that the selection of an efficient hydraulic alternative requires the realization of several experimental assemblies, whose results must be analyzed from the hydraulic point of view and incorporated in the experimentation stage to identify the best option of energy dissipation through various combinations. In order to properly implement the necessary hydraulic elements to obtain better results, the concepts applicable to the project are studied, such as energy dissipation, gates, dumps, holes and other parameters, which are useful in the development of the activities that are going to implement. The energy dissipaters are used to dissipate excess kinetic energy, which in many aspects can generate erosion, and in the case of the experimental channel can generate disturbances that directly affect the performance of the tests, giving results not very reliable from the point of view. hydraulic view due to the uncertainty that arises. The results of the devices or assemblies implemented during the experimentation are compared with the initial conditions, which gives a guideline to determine the progress of the activities and thus obtain the expected results.